Analysis of Humanistic Education: Unraveling Paulo Freire in Islamic Perspectives - Muwahidah Nur Hasanah; Agus Sriyanto; Evita Mita Nur Hana (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2023)
This study delves into the educational philosophy of Paulo Freire, emphasizing its humanistic roots and exploring its intersections with Christian, Marxist, existentialist, phenomenological, and personalist philosophies. Influenced by liberation theology figures like Gustavo Gutiérrez, Freire envisioned education as a tool for conscientization, aiming to cultivate critical awareness among the oppressed. Freire's humanistic approach faces criticism, particularly concerning the ambiguity of its goals and potential psychological disturbances. The research methodology is rooted in an extensive literature review, incorporating both primary and secondary data sources. Primary data stems from direct references relevant to the research topic, such as scholarly journals and articles, while secondary data is derived from existing literature to construct a solid conceptual framework. Appropriate data analysis tools aligning with research objectives are employed to systematically evaluate the collected information. This methodology aims to provide a comprehensive understanding of the theories and concepts essential to the research. The outcomes and discussions underscore the fundamental disparities between Freire's humanistic education and Islamic perspectives. While Freire advocates for critical consciousness and social liberation, Islam centers its education on the Quran and Hadith, emphasizing moral and spiritual responsibilities as Khalifah. Islam interprets freedom as the pursuit of goodness guided by divine revelations, rejecting liberal interpretations. The study concludes by accentuating the stark differences in worldview and values between Freirean humanism and Islamic education, shedding light on the diverse philosophical foundations underpinning these approaches.